Effects of female reproductive competition on birth rate and reproductive scheduling in a historical human population - Jenni E Pettay; Mirkka Lahdenperä; Anna Rotkirch; Virpi Lummaa (Oxford University Press, 2022)
Costly reproductive competition among females is predicted to lead to strategies that reduce these costs, such as reproductive schedules. Simultaneous births of coresident women in human families can reduce their infant survival, but whether such competition also affects overall birth rates and whether females time their pregnancies to avoid simultaneous births remain unknown, despite being key questions for understanding how intrafemale competition affects reproductive strategies. Here, we used detailed parish registers to study female reproductive competition in historical Finnish joint-families, where brothers stayed on their natal farms and sisters married out, and consequently unrelated daughters-in-law often coresided and competed for household resources. We quantified the time-varying effects of having reproductive-aged competitor(s) on a woman’s interval from marriage to first childbirth, on age-specific fertility, and on birth scheduling. Contrary to our hypothesis, the presence of one or several potential female competitors did not lead to longer first birth intervals or lower age-specific probability of reproduction. We also found no evidence that women would schedule their reproduction to avoid the real cost of simultaneous births on their offspring mortality risk; age-specific reproductive rates were unaltered by changes in the presence of other infants in the household. These results raise interesting questions regarding the evolution of fertility suppression in social mammals in different contexts, the costs and benefits of extended families for female reproductive success and strategies deployed, and the cultural practices that may help to avoid the negative outcomes of female reproductive competition in human families.